Model of forming a spatial-temporary radio frequency portrait of subscriber terminals in satellite communication systems monitoring - М. Балдычев; А. Босый; О. Гальцева; X. Цзян (Қарағанды университетінің хабаршысы. Физика сериясы)
Currently, the development of satellite communications systems (SCS) is associated with the development of signals of complex structure. The popularization and distribution of software-defined radio systems (Software-defined radio, SDR) are noted, which leads to a decrease of quality of functioning of the SCS. Promising areas of countering the unauthorized use of the time-frequency resource of the KA repeater are methods aimed at determining the location of subscriber terminals (ST) and analyzing the service and semantic parts of the transmitted message. Accounting for changes of physical parameters requires the use of a large amount of heterogeneous a priori data; it is not achievable task in practice. According to the theory of mathematical statistics, the approximation is used at solving problems of sample analysis. The result of the approximation is a spatio-temporal radio-frequency portrait (STRFP) of an ST participating in the formation of a group signal. Thus, the aim of the research is to develop a model of changing the physical parameters of a radio signal and to study the possibility of approximating physical parameters in order to form a spatio-temporal radiofrequency portrait of an ST SCS.